Sound propagation in the near and far-field of a broadband echolocating dolphin and a narrowband echolocating porpoise - Wei, Chong; Au, Whitlow; Ketten, Darlene; Vishnu, Hari; Ho, Abel Zhong Hao (Acoustical Society of America, 2019)
The echolocation signals emitted by odontocetes can be roughly classified into three broad categories: broadband high-frequency echolocation signals, narrowband high-frequency echolocation signals, and frequency modulated clicks. Previous measurements of broadband echolocation signals propagation in the bottlenose dolphin (Tursiops truncatus) did not find any evidence of focusing as the signals travel from the near to far-field. Finite element analysis (FEA) of high-resolution CT scan data was used to examine signal propagation of broadband echolocation signals of dolphins and narrowband echolocation signals of porpoises. The FEA results were used to simulate the propagation of clicks from phonic lips, traveling through the forehead, and finally transmission into the seawater. Biosonar beam formation in the near-field and far-field including the amplitude contours for the two species was determined. The finite element model was validated by finding the simulated amplitude contour in the horizontal plane was consistent with prior direct measurement results for Tursiops. Furthermore, the simulated far-field transmission beam patterns in both vertical and horizontal planes were also qualitatively consistent with results measured from live animals. This study shows that there is no evidence of convergence for either Tursiops or Phocoena as the sound propagates from near-field to far-field.